Komunikasi Antar Budaya Di Pondok Pesantren Kyai Syarifuddin - M. Zakaria Husni; Syamsul Hadi HM (Institut Agama Islam Syarifuddin Lumajang, 2021)
This study discusses intercultural communication that occurs at the Kyai Syarifuddin Islamic Boarding School. Islamic boarding schools are places where students stay or can be said where students learn the Koran. They come from various backgrounds. The phenomenon of intercultural communication in Islamic boarding schools is very interesting to discuss. The purpose of this study is to explain how the patterns, behaviors, and barriers to intercultural communication in Islamic boarding schools. This research uses a qualitative method, with a case study approach. The research location is the Kyai Syarifuddin Islamic Boarding School, Wonorejo Lumajang. This study collects data by means of field observations. In addition, in-depth interviews were also conducted with the administrators and several male students from different origins. Data analysis is done by reducing, presenting, and formulating conclusions. The results of this study students experience a reduction in uncertainty in several ways that are practiced in Islamic boarding schools which include, students maintain ethics in communicating behavior, second; the pattern of communication between individuals is communication with intimacy by using the Indonesian language which occurs in the third; The most prominent obstacle in the communication process is language. To be able to overcome language problems in Islamic boarding schools, the students always ask questions in Indonesian.Keywords: Communication, Culture, Uncertainty Reduction, Islamic Boarding School